Comparative microbial analyses of hydroponic versus in-soil grown Romaine lettuce obtained at retail - Zahra H. Mohammad; Isabelle do Prado; Sujata A. Sirsat (Heliyon, 2022)
The overarching goal of this study was to assess the microbiological profile of hydroponically grown Romaine lettuce and in-soil Romaine lettuce (organic and conventional). Thirty-six samples of hydroponic lettuce, seventy-two samples organic lettuce (thirty-six bagged lettuce and thirty-six non-bagged lettuce), and thirty-six conventionally grown lettuce was purchased from retail stores. A portion of each sample was analyzed for aerobic bacteria (APC), coliforms and E. coli, and yeasts and molds (YM). Another portion of each sample was enriched for Salmonella, E. coli O157:H7, Listeria monocytogenes, and Staphylococcus aureus, and confirmed with RT-PCR. No statistical differences were found in the microbial profile (P > 0.05) between the different farming practices. The APC, coliforms, E. coli, and YM counts were similar across bagged samples. The results demonstrated that APC and E. coli were significantly higher (P<0.05) in organic non-bagged samples compared to other practices. Salmonella and L. monocytogenes were detected in some organically and conventionally grown lettuce samples but were only detected in 3 hydroponically grown lettuce samples. This study indicated that hydroponically grown lettuce obtained at retail may have food safety risks similar to organic and conventional systems. These findings highlight the need for food safety training and educational programs.